Diffraction Plane Dependence of Micro Residual Stresses in Uniaxially Extended Carbon Steels - T. Hanabusa; A. Shiro; M. Refai; M. Nishida (Atom Indonesia, 2010)
In the stress measurement using X-ray or neutron diffraction, an elastic anisotropy as well as a plastic anisotropy of crystal must be carefully considered. In the X-ray and neutron diffraction stress measurement for polycrystalline materials, a particular {hkl} plane is used in measuring lattice strains. The dependence of an X-ray elastic constant on a diffraction plane is a typical example caused by an elastic anisotropy of the crystal. The yield strength and the work hardening rate of a single crystal depend on a crystallographic direction of the crystal. The difference in the yield strength and the work hardening rate relating to the crystallographic direction develops different residual stresses measured on each {hkl} diffraction after plastic deformation of a polycrystalline material. The present paper describes the result of the neutron stress measurement on uniaxially extended low and middle carbon steels. A tri-axial residual stress state developed in the extended specimens was measured on different kind of {hkl} diffraction plane. The measurement on the {110}, {200} and {211} diffraction showed that residual stresses increased with increasing the plastic elongation and the residual stresses on {110} were compressive, {200} were tensile and those on {211} were the middle of the former two planes. Received: 30 September 2010; Revised: 28 October 2010; Accepted: 1 November 2010